2021
DOI: 10.1515/multi-2020-0148
|View full text |Cite
|
Sign up to set email alerts
|

Language ideologies of emerging institutional frameworks of Mapudungun revitalization in contemporary Chile: nation, Facebook, and the moon of Pandora

Abstract: This article is a succinct approach to Mapudungun language ideologies and their development within the political and economic context of 21st century Chile. Social media have empowered Mapudungun language activists and intellectuals and helped them create digital communities, some with hundreds of thousands of followers, from which they establish and promote language policies, defined by themselves. Among the most relevant language ideologies found in the corpus, there is a representation of Indigenous languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
0
0
1
Order By: Relevance
“…In former analysis and observations that came out in the context of teacher training courses we offered (López García 2015, we demonstrated that the school curriculum, textbooks, dictionaries and other grammatization instruments (Auroux 1992) proclaim their respect and valuation of diversity but, paradoxically, school practices also reinforce the pyramidal normative structure (Alvarado 2023, Greusslich 2022, Méndez Gª de Paredes 2012 where Real Academia Española [the Spanish Royal Academy, hereinafter RAE] is the apex, and therefore, so is its linguistic authority and the variety of Madrid Spanish represented in its instruments. This situation replicates the mode of operation of late capitalism: celebrating identities and diversity while, in parallel, unifying cultures, labor markets and territorial exploitation; whereby, from this perspective, language is part of the exchange of goods and services (Blommaert 2010, Duchêne & Heller 2012, Gal 2012).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In former analysis and observations that came out in the context of teacher training courses we offered (López García 2015, we demonstrated that the school curriculum, textbooks, dictionaries and other grammatization instruments (Auroux 1992) proclaim their respect and valuation of diversity but, paradoxically, school practices also reinforce the pyramidal normative structure (Alvarado 2023, Greusslich 2022, Méndez Gª de Paredes 2012 where Real Academia Española [the Spanish Royal Academy, hereinafter RAE] is the apex, and therefore, so is its linguistic authority and the variety of Madrid Spanish represented in its instruments. This situation replicates the mode of operation of late capitalism: celebrating identities and diversity while, in parallel, unifying cultures, labor markets and territorial exploitation; whereby, from this perspective, language is part of the exchange of goods and services (Blommaert 2010, Duchêne & Heller 2012, Gal 2012).…”
Section: Introductionmentioning
confidence: 82%
“…The methodological strategies of glotopolitical perspective combine research on language ideologies (Pennycook 2008, Swiggers 2019, Woolard 2016 and models of critical discourse analysis (Blommaert 2010). Several investigations (see Arnoux 2016Arnoux , 2022Zavala 2021;Alvarado 2023) show how this combination of theoretical and methodological tools make it possible to comprehensively examine various sources of information linked to the school system: curriculum, schoolbooks, dictionaries, Grammar, etc. And, most importantly, it also allows us to recognize and weigh those school materials as instruments managed in a historical, political and technical environment.…”
Section: Theoretical Framework and Methodologymentioning
confidence: 99%
“…Esto para mantener, revalorizar y revitalizar sus lenguas en los cambiantes contextos sociopolíticos, económicos y culturales en los que se encuentran, recurriendo a nociones locales y desafiando las narrativas que los posicionan como pueblos y lenguas en vías de desaparición (cfr Davis, 2017;Olsen-Reeder, 2018;Unamuno et al, 2020). Estas acciones de revitalización, además de incorporar crecientemente las nuevas tecnologías y recursos en línea (Alvarado, 2021;Pinto, 2020), se conectan con proyectos de resistencia política, de desarrollo del bienestar general y de una continua descolonización en su conceptualización y puesta en práctica (Hinton et al, 2018;Stebbins et al, 2018). Estas acciones desafían en la práctica, además, la construcción histórica de la idea de nación y estado monolingüe.…”
Section: Lic áLvaro Ugueño Novoaunclassified